Digital Clinical Photography: Practical Tips - Mutalik, Sharad (Medknow Publications, 2010)
Photographs are the most preferred and easiest way of documentation of patient visual features. In aesthetic and cutaneous surgery, there is an increased need for proper photographic documentation, from a medicolegal view point. This article discusses the basic aspects of camera and photography which a dermatologist should be aware before he/she starts with clinical photography.